Baseline levels of microplastics in agricultural soils obscure the effects of additional microplastics from recycled fertilizers - Collin J. Weber; Dominika Kundel; Andreas Fliessbach; Else K. Bünemann; Moritz Bigalke (Microplastics and Nanoplastics)
Abstract Digestate from the recycling of various organic wastes in biogas plants is widely used as organic fertilizer for agricultural soils. Organic fertilizers contribute to microplastic loads, but it is not well constrained how they contribute to the overall accumulation of microplastic in agricultural soils. We investigated a field experiment in Switzerland fertilized since 2018 with liquid or solid digestate from a non-agricultural biogas plant. Microplastic particle concentrations (p) and characteristics were investigated in digestate fertilizers, digestate-treated soils and a control soil that did not receive organic fertilizers. Microplastics were extracted from the soil (two rounds of density separation (1.5 g cm− 3) and Fenton treatment), followed by µFTIR chemical imaging analysis with a size detection limit of 20 μm. We found median microplastic concentrations of 16,000 p kg− 1 (10,600–54,000 p kg− 1) in digestate fertilizers, 6,400 p kg− 1 (800–33,800 p kg− 1) in digestate-treated soils and 7,100 p kg− 1 in the control soil caused by a single outlier value or 5,600 p kg− 1 when excluding the outlier. Particle sizes and polymer compositions differed between digestate fertilizers and soils. Topsoil (0–20 cm) microplastic stocks varied from 1.8 to 3.8 × 106 p m− 3. The calculated inputs from the digestate application contributed only 0.9–4.0% to the total microplastic stocks which led to the case that digestate microplastic inputs were not detectable against the variation of the stocks. The study highlights those substantial high concentrations of microplastic might already occur in many soils, due to previous microplastic inputs over several decades from e.g., recycled fertilizer application like sewage sludge or from other diffuse sources. Whilst it was observed from the fluxes that digestate can be a substantial source of microplastics to soils, the comparatively short time of application and the high background at our investigated sites leads to a obscured effect where digestate inputs serve a limited function.